Crack Growth Patterns of Aluminum Tubular Specimens Subjected to Cyclic Tensile Loads - Abatta-Jacome, Lenin; Caminos-Gámez, Luis Francisco; González-Herrera, Antonio; García-Manrique-Ocaña, José Manuel (MDPI, 2024)
This study presents a detailed analysis of a fatigue test campaign in order to identify different crack patterns. It was conducted on 6061-T6 aluminum tubular specimens featuring an internal diameter of 10mmand different thicknesses (2, 3 and 4 mm). These specimens were subjected to cyclic tensile loads with a load ratio of R = 0.1, utilizing a sinusoidal load function at a frequency of 3 Hz. The investigation examines the crack growth rates, the stress intensity factor, and the final and intermediate fracture zones by applying overloads in some cases. The differences with two-dimensional specimens and the importance of this study for the interpretation of results with biaxial loading states are highlighted. The different states of crack growth detected are analyzed using artificial vision techniques. The differences between the exterior and interior faces of the specimen are revealed, and a series of states prior to the formation of the radial crack front expected in these specimens are identified.
Keywords: Materiales - Fatiga; Aluminio; Fatigue crack growth; SEM; Tubular specimen; Cyclic tensile loads